GENDER DECONSTRUCTION IN GEN Z SOCIAL MEDIA: A STUDY ON TIKTOK ACCOUNTS BEAUTY INFLUENCER @AKUNBARUKAREL - Rositah, Nila Dwi Noor; Dharma, Ferry Adhi Dharma (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the deconstruction of gender identity presented by @akunbarukarel on TikTok and how it challenges conventional understandings of masculinity and femininity in the digital sphere. Method: The research applies Jacques Derrida’s theory of deconstruction within a qualitative framework, utilizing observation, interviews, and content analysis to examine gender representation and audience reception. Results: The findings indicate that Karel embodies a fluid and inclusive gender identity, disrupting binary categorizations and fostering discourse on gender diversity within social media spaces. The content is largely embraced by Gen Z audiences, although it faces resistance from conservative groups. Moreover, Karel’s gender-fluid expression not only generates social influence but also creates economic opportunities through collaborations with beauty brands, highlighting the intersection of identity, culture, and commerce. Novelty: This study contributes new insights into how TikTok functions as a cultural arena where deconstructed gender identities are negotiated, normalized, and commercialized, offering a dynamic narrative that redefines gender discourse in contemporary digital society.